Innovations and challenges in identity research - Block, David 1956- (Abingdon, Oxon Routledge, 2022)
Innovations and Challenges in Identity Research examines established and emergent issues within identity research.

This innovative book adopts a disciplinary transcendent approach, drawing on a range of social science, humanities and human science disciplines on the way to a detailed consideration of:

• the history of identity as a construct
• the components of a poststructuralist/social constructivist approach to identity
• the prospect of a Marxist political economy approach to identity
• the interrelationship between structure and agency and a model of structuring spheres
• an expanded version of positioning theory
• the digital universe as the future of identity research.

Leading researcher David Block provides a personal take on this key topic of study in applied linguistics and explains why and how discourse analysis is still a useful means through which we can understand identity today. The book is essential reading for students and academics studying and researching within the area of language and identity.
Preface -- Revisiting identity: A short, selective history -- Key elements in the poststructuralist/social constructivist　approach to identity -- Towards a Marxist approach to identity: From recognition and redistribution debates to a historical materialist view of being in the world -- From structure and agency to structuring spheres -- Expanding positioning theory -- Applying the expanded model of positioning theory: An example -- Conclusion
Includes bibliographical references and index.
Keywords: Identity (Psychology) -- Social aspects; Sociolinguistics; Applied linguistics; Discourse analysis -- Social aspects